The role of cognitive and personality factors in youth deliberate self-harm: a systematic review - Kpeno, Audifax; Sahoo, Surjeet; Sahu, Amiya Krushna; Sahu, Pratap Kumar; Bagson, Ernest (International Journal of Research in Medical Sciences, 2024)
This systematic review aims to investigate the relationship between cognitive factors, emotional tendencies, and personality traits contributing to deliberate self-harm (DSH) behaviour among youth. This systematic review followed the preferred reporting items for systematic reviews and meta-analyses guidelines. Literature searches were conducted in March 2024 using Scopus, PubMed, and Google Scholar, focusing on "deliberate self-harm," "youth," "cognitive factors," and "personality profiles." The search was limited to articles in English from medicine, psychology, and social sciences, published in the U. S., Canada, Australia, the U. K., and New Zealand. Articles were selected based on their relevance to youth DSH and related cognitive constructs, excluding those focused on suicidal ideation. A narrative synthesis was performed, and study quality was assessed using the Cochrane risk of bias tool. A total of 21 articles were identified and included in the final review. Emotional regulation emerges as crucial in preventing DSHing behaviours, with early detection facilitated by screening for impulsivity, sensation-seeking, and emotional dysregulation. Prevention strategies targeting specific cognitive patterns and personality traits associated with self-harm are informed by insights from this review, drawing from diverse studies. Limited yet promising evidence underscores the need for further research to elucidate these relationships. Additionally, significant correlations between specific online behaviors and DSH among youth are noted. Understanding these cognitive constructs and personality traits can offer timely support and guidance in clinical practice, potentially leading to more effective, personalized interventions for reducing DSH behaviour among youth. Prospero registration no.: crd42024525239.